Indicators based on registers and administrative data for breast cancer: routine evaluation of oncologic care pathway can be implemented. Issue 1 (20th August 2015) - Andreano, Anita; Anghinoni, Emanuela; Autelitano, Mariangela; Bellini, Aldo; Bersani, Maurizio; Bizzoco, Sabrina; Cavalieri d'Oro, Luca; Decarli, Adriano; Lucchi, Silvia; Mannino, Salvatore; Panciroli, Emerico; Rebora, Paola; et al.
Abstract: Rationale, aims and objectives: Assuring the best standards of care – in a sustainable way – in chronic diseases as breast cancer is nowadays an important challenge for any health system. The aim of this study was to present the methodology used to define a set of quality indicators, computable from administrative data for the pathway of care of breast cancer, and its application at a population level. Method: The cohort of 2007–2009 incident cases of breast cancer was identified through a network of six cancer registers in Northern Italy. Cases of sarcoma and lymphoma, patients with multiple primary cancers and those metastatic at diagnosis were excluded; 9614 women were retained for the analysis. For each indicator, the sub‐cohort of women eligible for the diagnostic/therapeutic procedures was identified and calculations were performed through record linkage between the cohort and sources of health information. Data on potential available confounders or prognostic factors were also collected. Results: For a few indicators, such as cyto‐histological assessment before surgery (62%) and intensive follow‐up (79%), deviation from recommendations was evident. Younger patients (≤50 years) more frequently needed a short term re‐intervention, while older patients less frequently underwent reconstructive surgery and received palliative care. Several indicators had a great variability across hospitals. In some cases, this heterogeneity appeared to be related to the hospital size, with high‐volume hospitals being more compliant to guidelines. Conclusion: It is possible to evaluate the quality of cancer care delivered in clinical practice in recent years, in order to implement interventions aimed to improve adherence to international standards of care.